Regulatory T cell therapies: from patient data to biological insights - Rodrigues, Kameron B.; Eggenhuizen, Peter J.; Bacchetta, Rosa; Good, Zinaida (Frontiers in Immunology, 2025)
Regulatory T cell (Treg) therapies are emerging as powerful tools for treating autoimmune and inflammatory diseases, preventing graft-versus-host disease (GvHD), and promoting organ transplant tolerance. Building on the identification of chimeric antigen receptor (CAR)-expressing Tregs as a correlate of poor patient outcomes in CD19-CAR T cell therapy, this review examines strategies for learning from clinical samples and data to improve Treg therapies. We highlight current and next-generation Treg modalities, including polyclonal, antigen-specific, converted, TCR-engineered, and CAR-engineered Tregs, provide a comprehensive overview of Treg clinical trials, and evaluate the evolving toolkit for in vivo Treg monitoring. Emphasis is placed on advanced immunomonitoring technologies, such as single-cell multi-omic profiling, epigenetic analysis, and spatial transcriptomics, which enable precise characterization of Treg persistence, function, and lineage stability. By integrating insights from adoptive T cell therapies and cutting-edge multi-omic platforms, this review outlines how Treg therapies can be optimized as “living drugs” capable of establishing immune tolerance across diverse clinical contexts.